Experimental investigation on laser micro-machining of Al 7075 Alloy. (November 2018) - Mandal, K.K.; Kuar, A.S.; Mitra, S.
Highlights: Literature survey focused on Al 7075 alloy for the Nd:YVO4 laser beam machining set-up. Laser beam power, pulse frequency and scanning speed – input. kerf width, HAZ and angle deviation – output. L9 OA. Processing Parameters measured by optical microscope (STM 6) and AFM (Nanosurf Easyscan 2). S/N ratio plots determine optimum condition. ANOVA, confirmation experiment conducted to verify predicted model value. SEM observation performed under different machining conditions to study the cutting zone microstructure. Abstract: Light metal alloys have low density, high stiffness and high strength to weight ratio. These alloys are of great importance in engineering industries for construction of transportation equipment, aircraft parts, aerospace, military & missile application, etc. Nowadays, aluminium alloys are becoming the world's second most used material after steel. In this present research work, Al 7075 alloy sheet of 2 mm thickness has been micro-machined of square shape by using Nd:YVO4 pulsed laser of maximum capacity of 9.4 W with spot beam diameter of 50 μm, laser pulse width of 4.2 ns and wavelength of 1.064 nm. The machining quality in terms of kerf width, HAZ and surface roughness are observed at different parametric combination of the influencing parameters, namely laser beam power, pulse frequency and scanning speed. Taguchi methodology (L9 OA) is utilized for the design of experiment. The responses are also optimized and analyzed by Taguchi methodology. The experimental results are then verified and justified the significance of the processing parameters following ANOVA and confirmation experiment. The confirmation test shows the improvement of the responses over all the experimental result. SEM has also been observed for microstructure study.